Migration, remittances, and wage-inflation spillovers: The case of Albania - Lorena Skufi; Meri Papavangjeli; Adam Gersl (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Motivated by migration phenomena and wage-inflation spillovers, we investigate the relationship between the two and the inflationary remittances built-in pressures. We establish a feedback loop between migration and inflation, and specify a simple dynamic model to identify the pass-through. Our empirical approach focuses on the wage Phillips Curve, price setting under monopolistic competition, and state space model for the natural unemployment rate. Our estimates suggest that overshooting inflation and tight labor market conditions increase wage-inflation sensitivity. A continuous decline of population by 1% leads to 98 basis points (BP) of inflation pressures in the short-run and 23 BP in the long-run. Remittances induce excessive pressures by 18 BP on inflation. Supportive schemes such as an older retirement age and higher labor force participation rate can partially mitigate inflationary.
Keywords: J11; J21; J31; E24; E31; 330; labor market; demographics; inflation; wage; remittances; feedback-loop